The effect of manufacturing defects and license plate on the energy efficiency of solar vehicles - Burak İpek; Mehmet Yıldız; Tunahan Akış; Aytaç Gören (Academia Green Energy)
In recent times, research on the energy efficiency of solar vehicles has gained momentum. A significant component of the mentioned efficiency is the vehicle’s resistance to airflow. From this perspective, the aim of this study is to investigate the effect of manufacturing defects on the aerodynamic performance of solar vehicles. An analysis of these manufacturing defects at different vehicle speeds has been conducted. In this study, the SOLARIS 11 (S11) solar vehicle has been analyzed in four scenarios: (i) computer-aided design (CAD) version, (ii) CAD version with manufacturing defects, (iii) with a license plate, and (iv) with both manufacturing defects and a license plate. In addition, these four different scenarios have been evaluated separately for vehicle speeds of 60, 90, and 120 km/h. In conclusion, with manufacturing defects, the variation in power consumption of the solar car increased by an average of 24.55–29.09% according to the ideal CAD model. This increase is found to cause a reduction in the vehicle’s range by 18.31–37 km. Power consumption of the vehicle was calculated as 237 W for the CAD model, 246 W for the model that has manufacturing defects, and 309 W for the model that has both manufacturing defects and a license plate at 60 km/h. Similarly, power consumption values are calculated as 1,692, 2,167, and 2,214 W at 120 km/h. Additionally, the increase in power consumption caused by the license plate in the absence of manufacturing defects has been examined as a separate section.